The Girl Who Survived - Jackson, Lisa (Thorndike, Maine : Center Point Large Print, 2022)
"All her life, shes been the girl who survived. Orphaned at age seven after a horrific killing spree at her familys Oregon cabin, Kara McIntyre is still searching for some kind of normal. But now, twenty years later, the past has come thundering back. Her brother, Jonas, who was convicted of the murders, has unexpectedly been released from prison. The press is in a frenzy again. And suddenly, Kara is receiving cryptic messages from her big sister, Marlie -- who hasnt been seen or heard from since that deadly Christmas Eve when she hid little Kara in a closet with a haunting, life-saving command: Dont make a sound. As people close to her start to die horrible deaths, Kara, who is slowly and surely unraveling, believes she is the killers ultimate target. Kara survived once. But will she survive again? How many times can she be the girl who survived?"--
Keywords: Massacre survivors -- Fiction; Homicide -- Fiction; Survival -- Fiction; Families -- Fiction; Siblings -- Fiction; Murder -- Fiction; Oregon -- Fiction; Detective and mystery fiction; Thrillers (Fiction)